Promoting active aging with the Oro Miel group, located in La Granja, Palmares - Barrantes Gutiérrez, Melissa (2025)
Introduction: This article systematizes the experience of community practice carried out in the community of La Granja in the canton of Palmares, Alajuela, Costa Rica. This was developed within the framework of the OT1078 Theory and Practice of Social Work IV course, part of the bachelor’s degree in social work at the University of Costa Rica, Western Regional Campus. It highlights the importance of promoting community self-management to encourage active aging in communities.  Main objective: The objective of the article is to systematize the experience of community participation and the promotion of active aging with the Oro Miel group located in La Granja, Palmares, Alajuela, Costa Rica, with the aim of strengthening future community practices in social work using the socio-educational promotional model. Methodology: For the community diagnosis, Participatory Action Research (PAR) was used to raise awareness among the community about problems to be attended, which was key to the intervention project. A promotional socio-educational model was used to provide information and training, promoting the comprehensive development of the communities. Working with groups facilitated the active participation of older adults in Oro Miel, who became agents of research into their own reality. Workshops were held to validate the project and present results, where certificates of participation were awarded. Continue reading in the article